Jurnal Kata: perceptual dialectology" northerners and southerners view of different American dialects - Nurenzia Yanuar, Kamola Azimova; Doung Nguyen (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
American englist, also know as US englist. is a set dialects in the englist language mostly used in the US